New family of nonionic gemini surfactants: Determination and analysis of interfacial properties - Castro, Mariano Javier Luis (2002)
The interfacial properties of a new family of nonionic surfactants derived from alkyl glucosides were studied. The physicochemical parameters of these dimeric compounds were compared with those of their monomeric counterparts. The effect of the position of the linkage, the anomeric configuration, the spacer functionality, and the spacer type (rigid or flexible) on the behavior of these surfactants was analyzed for a short-chain (butyl) series of compounds. Slight structural variations have a significant influence on their properties. The maximum length of the hydrophobic chains for obtaining gemini surfactants with improved efficiencies compared to those of the starting monomeric alkyl glucosides was estimated.